2022
DOI: 10.1007/s10899-022-10158-y
|View full text |Cite
|
Sign up to set email alerts
|

How do Gambling Providers Use the Social Network Twitter in Germany? An Explorative Mixed-Methods Topic Modeling Approach

Abstract: This study examines the social media activities of gambling providers in Germany, focusing on the platform Twitter. A collection of 34.151 tweets from 13 Twitter accounts was made, representing casinos, sports betting, state lotteries, social lotteries and lottery brokers. We apply an explorative mixed-methods approach, integrating a summative content analysis together with a semi-supervised guided topic modeling approach, to analyse frequency, number of followers, interaction and content of Twitter messages, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
(86 reference statements)
1
0
0
Order By: Relevance
“…This proportion is similar in other countries e.g. 33% in Germany (Singer et al 2022) and 48% in Canada (Wheaton et al, 2024). Houghton et al (2019) found that around 8% of social media posts by gambling providers used "brand engagement strategies" whilst Smith and Nairn (2019) found that UK gambling content marketing reaped much more engagement on Twitter (i.e.…”
Section: Gambling Advertising On Social Media: What We Knowsupporting
confidence: 75%
“…This proportion is similar in other countries e.g. 33% in Germany (Singer et al 2022) and 48% in Canada (Wheaton et al, 2024). Houghton et al (2019) found that around 8% of social media posts by gambling providers used "brand engagement strategies" whilst Smith and Nairn (2019) found that UK gambling content marketing reaped much more engagement on Twitter (i.e.…”
Section: Gambling Advertising On Social Media: What We Knowsupporting
confidence: 75%